The Effect of the Development of Physics Teaching Materials in Improving Student Concept Understanding - Rudi Haryadi; Heni Pujiastuti; Hanifa Nuraini Al Kansaa (Universitas Muhammadiyah Enrekang, 2022)
Physics is a subject that is considered difficult by students because they cannot understand the concept of the material being taught. Therefore, the teacher must create an effective physics learning atmosphere in the classroom. One of them is by providing a teaching material that will be used in learning physics. The purpose of writing this article is to determine the effect of developing physics teaching materials in increasing students' understanding of concepts. The research method used is the literature study method. The results of this study indicate that there is an influence on increasing students' conceptual understanding of physics material by using the development of teaching materials.